CMIP5 historical simulations (1850–2012) with GISS ModelE2. (10th June 2014) - Miller, Ron L.; Schmidt, Gavin A.; Nazarenko, Larissa S.; Tausnev, Nick; Bauer, Susanne E.; DelGenio, Anthony D.; Kelley, Max; Lo, Ken K.; Ruedy, Reto; Shindell, Drew T.; Aleinov, Igor; Bauer, Mike; et al.
Abstract Observations of climate change during the CMIP5 extended historical period (1850–2012) are compared to trends simulated by six versions of the NASA Goddard Institute for Space Studies ModelE2 Earth System Model. The six models are constructed from three versions of the ModelE2 atmospheric general circulation model, distinguished by their treatment of atmospheric composition and the aerosol indirect effect, combined with two ocean general circulation models, HYCOM and Russell. Forcings that perturb the model climate during the historical period are described. Five‐member ensemble averages from each of the six versions of ModelE2 simulate trends of surface air temperature, atmospheric temperature, sea ice and ocean heat content that are in general agreement with observed trends, although simulated warming is slightly excessive within the past decade. Only simulations that include increasing concentrations of long‐lived greenhouse gases match the warming observed during the twentieth century. Differences in twentieth‐century warming among the six model versions can be attributed to differences in climate sensitivity, aerosol and ozone forcing, and heat uptake by the deep ocean. Coupled models with HYCOM export less heat to the deep ocean, associated with reduced surface warming in regions of deepwater formation, but greater warming elsewhere at high latitudes along with reduced sea ice. All ensembles show twentieth‐century annular trends toward reduced surface pressure at southern high latitudes and a poleward shift of the midlatitude westerlies, consistent with observations.